2020
DOI: 10.31234/osf.io/tbd2e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intra-individual Variability in Narrative Identity: Complexities, Garden Paths, and Untapped Research Potential

Abstract: This paper introduces key concepts for studying intraindividual variability in narratives (Narrative IIV). Narrative IIV is conceptualized in terms of sources of within person variation (events and audiences), and dimensions of variation (structural and motivational/affective dimensions of narratives). Possible implications of narrative IIV for well-being and self and social development are outlined. Considering narrative IIV leads to complexity in both theory and method, raising the issue of whether some aven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
3
7
0
Order By: Relevance
“…Indeed, comparing the moderate correlation between thematic oral and total written narrative coherence over a 4-month time period that was observed in the current study, r = 0.33, to an earlier observed correlation of two oral narrative coherence measurements over a 5-month time period, r = 0.48, (Vanaken et al, unpublished), suggests that there are in fact also event- and modality-specific aspects in addition to the stable narrative style that can impact coherence to some extent. This is in line with earlier work ( Fivush et al, 2017 ; McLean et al, 2017 ; Adler et al, 2018 ; Waters et al, 2019 ; Pasupathi et al, 2020 ). Future research is nonetheless needed to investigate the extent to which each aspect adds to the equation and can explain parts of the variance in coherence, by comparing narratives across time, event, modality, etc.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Indeed, comparing the moderate correlation between thematic oral and total written narrative coherence over a 4-month time period that was observed in the current study, r = 0.33, to an earlier observed correlation of two oral narrative coherence measurements over a 5-month time period, r = 0.48, (Vanaken et al, unpublished), suggests that there are in fact also event- and modality-specific aspects in addition to the stable narrative style that can impact coherence to some extent. This is in line with earlier work ( Fivush et al, 2017 ; McLean et al, 2017 ; Adler et al, 2018 ; Waters et al, 2019 ; Pasupathi et al, 2020 ). Future research is nonetheless needed to investigate the extent to which each aspect adds to the equation and can explain parts of the variance in coherence, by comparing narratives across time, event, modality, etc.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, different measurements of coherence are observed to be moderately correlated within individuals over time and event-type (McLean et al, 2017;Waters et al, 2019;Vanaken et al, unpublished). This is line with the idea that coherence is suggested to be partly determined by event-specific factors (e.g., type of event: Banks and Salmon, 2013; emotional intensity: Rubin et al, 2011) and narration-specific factors (e.g., context of sharing: Bavelas et al, 2000;Pasupathi, 2001), yielding a certain extent of intra-individual variability (Fivush et al, 2017;McLean et al, 2017;Waters et al, 2019;Pasupathi et al, 2020). For instance, both inherent differences between writing and speaking (e.g., Grysman, 2015), as well as social-contextual differences that are associated to different modalities (Bavelas et al, 2000;Pasupathi, 2001;Alea and Bluck, 2003) could impact the narrative.…”
Section: Associations Between the Coherence Of Oral And Written Narrativessupporting
confidence: 88%
See 2 more Smart Citations
“…It also reflects variable elements that include, for example, the individual's developmental period (coherence increased in this study over time in a group of emergent adults and the increase was not dependent on repetition of the same event, see also literature on cognitive maturation: Bohn & Berntsen, 2008;Köber et al, 2015;Reese et al, 2011), the event-processing time (coherence was higher for events that were concluded compared to ongoing events, see also Fivush et al, 2017;Waters et al, 2019), particular event characteristics (valence: coherence is often higher for narratives about negative events, see also: Vanderveren et al, 2019;event type: Banks & Salmon, 2013), and specific characteristics of the social context (listener's behaviour, social reinforcement: Bavelas et al, 2000;Pasupathi, 2001;Pasupathi & Rich, 2005). Summarised, this study provides support for the idea that there is a combination of an intra-individual stability as well as variability component to coherence, rather than coherence being either a characteristic of only the specific event or only the individual (Adler et al, 2018;Fivush et al, 2017;McLean et al, 2017;Pasupathi et al, 2020;Waters et al, 2019).…”
Section: Discussionsupporting
confidence: 55%